2017
DOI: 10.1111/ajt.14020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antiviral Prophylaxis for the Prevention of Epstein–Barr Virus–Associated Posttransplant Lymphoproliferative Disease in Solid Organ Transplant Recipients: A Systematic Review

Abstract: The role of antiviral prophylaxis for the prevention of posttransplant lymphoproliferative disease (PTLD) remains controversial for solid organ transplantation (SOT) recipients who are seronegative for Epstein-Barr virus (EBV) but who received organs from seropositive donors. We performed a systematic review and meta-analysis to address this issue. Two independent assessors extracted data from studies after determining patient eligibility and completing quality assessments. Overall, 31 studies were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 74 publications
(99 reference statements)
4
71
1
2
Order By: Relevance
“…A recent systemic review from AlDabbagh et al. did not show any benefit of antiviral prophylaxis in prevention of PTLD in high‐risk solid organ transplant recipients . While most of our patients developed EBV viremia on prophylaxis, only one patient developed PTLD.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A recent systemic review from AlDabbagh et al. did not show any benefit of antiviral prophylaxis in prevention of PTLD in high‐risk solid organ transplant recipients . While most of our patients developed EBV viremia on prophylaxis, only one patient developed PTLD.…”
Section: Discussioncontrasting
confidence: 52%
“…In a recent multicenter trial, Hocker et al found a lower incidence of EBV viremia in high-risk pediatric KTx recipients who received valganciclovir/ganciclovir prophylaxis 19. A recent systemic review from AlDabbagh et al did not show any benefit of antiviral prophylaxis in prevention of PTLD in high-risk solid organ transplant recipients 20.…”
mentioning
confidence: 99%
“…87 Much of the viral load is believed to be from latent EBV, against which these drugs are not as effective, since EBV-encoded protein kinase is not expressed. 94 We do not currently have any vaccines that are effective for prevention of EBV infection. Small randomized trials of cytomegalovirus (CMV)-Ig alone or ganciclovir ± immune globulin did not show significant differences in PTLD incidence, 89,90 although a small randomized trial of valganciclovir suggested a small benefit, needing validation.…”
Section: Screening Recommendations and Preventionmentioning
confidence: 99%
“…91 Some epidemiologic studies suggest that antiviral agents, 32,92 or the use of immunoglobulins such as CMV-Ig, 93 reduce the PTLD risk, but a recent systematic review found no differences. 94 We do not currently have any vaccines that are effective for prevention of EBV infection. One vaccine against EBV envelope glycoprotein gp350 that was tested was not successful.…”
Section: Screening Recommendations and Preventionmentioning
confidence: 99%
“…A systematic review of 31 studies showed no significant difference in the rate of EBV-associated PTLD among SOT recipients who received prophylaxis (with acyclovir, ganciclovir, valacyclovir, or valganciclovir), compared to those receiving no prophylaxis. 9 A large retrospective study showed reduced short-term (within 1 year) incidence of PTLD with use of anticytomegalovirus immunoglobulin after renal transplant, but no difference long-term. 10 Treatment involves immunomodulation and chemotherapy with or without radiotherapy, with a concurrent goal of preserving allograft function.…”
Section: Sectionmentioning
confidence: 99%